Implementation of Road Safety Countermeasures in Four Cities to Reduce the Harmful Effects of Alcohol: A Progress Report - Fell, James C; Achoki, Tom; DeJong, William; Fisher, Deborah A (Archives of Clinical and Biomedical Research, 2022)
Background: Beginning in 2016, the Anheuser-Busch InBev Foundation (ABIF) provided funding to six pilot cities to implement evidence-based interventions to reduce the harmful use of alcohol and its deleterious consequences such as alcohol-impaired driving. The cities receiving funding are Alexandra Township in Johannesburg, South Africa; Brasilia, Brazil; Columbus, Ohio, United States; Jiangshan, China; Leuven, Belgium; and Zacatecas, Mexico. Methods: Four of the city pilot coalitions are implementing a wide array of interventions to deter Driving Under The Influence (DUI). Columbus made efforts to get more judges to apply Ohio’s alcohol ignition interlock law and implemented and evaluated a Safe Rides program. Brasilia increased the number of roadside checkpoints and planned an educational campaign about the dangers of impaired driving to be delivered at bars by firefighters and paramedics. Alexandra expanded and upgraded the Metropolitan Police Department’s Alcohol Evidence Center (AEC). In Zacatecas, among other interventions, a new Driving While Intoxicated (DWI) facility is being constructed to expedite case processing and adjudication. Results: In ColumFrebus, the evaluation of the Safe Rides program showed an estimated reduction of 2.9 impaired driving crashes but also an average increase of 0.4 alcoholic drinks per program participant. There was a reduction in harmful alcohol use of .02% in 2017 associated with the Safe Rides campaign, but with no carryover to 2018. In Brasilia, the combined effect of the road safety measures and other factors resulted in a 35% decrease in traffic deaths between 2016 and 2019. In Alexandra, there were 46 fatal crashes over the Easter weekend in 2018, 25 fatal crashes in 2019 (46% reduction), and 3 fatal crashes in 2020 (88% reduction from 2019). To date, Zacate